Analisis Kecerdasan Emosional Siswa Sekolah Menengah Atas - Nursasih, Isna Daniyati (Universitas Galuh, 2023)
Emotional intelligence is an ability that every student needs to have in participating in the learning process. This research was conducted on class XII students of SMAN 1 Rancah to determine their emotional intelligence mastery category. This research does not look at gender as a comparison material for categories of mastery of emotional intelligence. The research instrument used a questionnaire from Goleman with a Likert scale. There are five indicators of emotional intelligence, namely recognizing one's emotions, managing emotions, motivating oneself, recognizing other people's emotions and building relationships. The study results show that students in each indicator are in the medium category. It is rare to find students in the low category, as well as those in the high category.